DESIGN OF A DIESEL ENGINE CONTROL SYSTEM TO CHANGE THE NUMBER OF INJECTION AND THE EFFECTS OF MULTI PHASE INJECTION ON NOX EMISSION LEVELS AND THE PERFORMANCE - Ergenc, Alp Tekin; Ergenc, Ali Fuat; Olgun, Burak; Ravali, Fatih (YILDIZ TECHNICAL UNIV, 2015)
Improvements of combustion in diesel engines are directly related to the combustion of the mixture formation. Mixture formation in diesel engines is provided with pulverizing the fuel and mixing with the air in the cylinder, thus good combustion occurs. In addition, the combustion process and mixture of formation are affected by injection system parameters such as start and finish timing of the injection, injection duration, injection pressure, injection beam and number. etc. In this context, given the importance of mixture formation in fuel injection systems, an engine that controls the fuel feed can be used in alternative fuels and emission treatment studies. The fuel injection duration determines the start time of combustion as crank angle and also affects the status change of the intake air and the change of ignition delay time of the combustion. The injection of the fuel quantity and duration can be controlled more effectively and liberally with the common rail injection system than using mechanical injection pump in diesel engines. In the common rail injection system the timing and duration of the current applied to the injectors determined by a controller using processed the data received from a variety of sensors and to optimize the operating point. Taking into consideration the sooty running of diesel engines caused by excessive fuel and an increase in NOx emissions by high temperature inside the cylinder, the effects of these parameters on NOx by changing the preliminary injection and injection characteristics on the injected fuel into the cylinder will be discussed in this study.
Keywords: Diesel engine; NOx; injection; advance; plc; COMBUSTION; PRESSURE; STRATEGIES; PARAMETERS; QUANTITY; Engineering